Effect of L-Carnitine and Vegetable Fat on Broiler Breeder Fertility, Hatchability, Egg Yolk and Serum Cholesterol and Triglyceride - Adabi, Sh. Golzar; Moghaddam, Gh.; Taghizadeh, A.; Nematollahi, A.; Farahvash, T. (International Journal of Poultry Science, 2006)
The effect of two dietary levels of L-carnitine and vegetable fat powder on broiler breeder fertility, hatchability, egg yolk and serum cholesterol and triglyceride was studied. Two hundred fifty female and twenty five male (Classic Hubbard parent stock) were distributed randomly in five groups of 50 with five replicate of 10 females and one male. Two levels of L-carnitine 0, 60 ppm (for females) and 0, 500 ppm (for males) and vegetable fat powder (0, 1.5%) and a diet with high lysine and methionine (0.3%) fed for both of male and female within one of treatment were used in a complete random design of treatments. The parameters as hatchability, fertility, egg weight, albumen height, Haugh unit, color of yolk, shell thickness, shell strength, yolk weights, egg yolk and serum cholesterol and triglyceride were measured. No significant differences were observed in external and internal egg quality. Supplemented diet with L-carnitine had effect on hatchability (P< 0.05) and fertility (P< 0.01). L-carnitine had no effect on egg production except on fifth and sixth weeks (P< 0.01). None of experimental diet had no effect on male serum cholesterol, serum triglyceride in both sex and total yolk cholesterol but L- carnitine had effect on female serum cholesterol (P< 0.05). L- carnitine had decreased egg yolk cholesterol (mg/gr) (P< 0.05). Yolk weight increase in response to dietary supplementation of L-carnitine(P< 0.05) and L-carnitine content of egg yolk increase with L-carnitine supplementation (P< 0.05).